Peninjauan Parameterisasi Wind Gust saat Kejadian Konvektif dan Non-Konvektif: Studi kasus di Bandara Internasional Kertajati - Muhammad Rafid Zulfikar; Muhammad Rais Abdillah; Prasanti Widyasih Sarli (Universitas Andalas, 2023)
Wind gusts (gusts) are sudden increases in wind speed that potentially cause severe damage to infrastructure. Gusts occur within several seconds but numerical weather models typically predict future wind with a time step of tens of seconds or minutes. Therefore, a parameterization is needed to estimate gust. Gusts can be produced convectively and non-convectively depending on the presense of thunderstorm. The gust parameterization schemes may perform differently in both cases. In this study, five wind gust parameterization schemes were evaluated at the Kertajati International Airport. Based on simulations of three convective gust and three non-convective gust events using several evaluation metrics, we find that the best scheme for non-convectively driven gusts is the Turbulent Kinetic Energy (TKE) scheme, while the Hybrid scheme performs best for convectively driven gusts. However, the performance of Hybrid scheme during non-convective event is not so far behind TKE scheme. The Hybrid scheme was developed to work on both non-convective and convective events and this capability is evidently shown. The result could be useful to develop mitigation measures for strong wind incident that frequently occurs in Indonesia.